Two cultural myths from the upper amazon: tales of a humanized world (2011)
Despite cultural, linguistic and geographic differences, the Witoto and Tikuna indigenous peoples share mythical episodes, which happen to be at the base of their everyday activities and their rituals of relationship with the forest and its masters. This text highlights some similarities in the myths of origin of both groups, which moves us to find out more about the complementarity between actions of the mythical twins, and the restoration and organization of the world for human survival, knowledge and values.